Acute risk factors for suicide attempts and death: prospective findings from the STEP‐BD study. (27th May 2016) - Ballard, Elizabeth D; Vande Voort, Jennifer L; Luckenbaugh, David A; Machado‐Vieira, Rodrigo; Tohen, Mauricio; Zarate, Carlos A
Abstract : Objectives: Suicide is unfortunately common in psychiatric practice, but difficult to predict. The present study sought to assess which clinical symptoms increase in the months before suicidal behavior in a sample of psychiatric outpatients with bipolar disorder. Methods: Data from the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP‐BD) trial were used. A total of 103 participants who attempted suicide or died by suicide during the trial were included; a 15% random sample of the remaining participants (n = 427) was used as a comparison sample. Linear mixed models in the six months before suicidal behavior were conducted for each of five proposed acute risk factors for suicidal behavior. Participants were assessed using the Clinical Monitoring Form (CMF) at each visit for the following potential acute risk factors for suicidal behavior: suicidal ideation, loss of interest, anxiety, psychomotor agitation, and high‐risk behavior. Results: Each of the five symptoms was elevated overall in individuals who engaged in suicidal behavior (p < 0.05). The severity of both suicidal ideation and loss of interest significantly increased in the months before suicidal behavior (p < 0.001). Anxiety demonstrated comparable effect sizes across multiple models. Psychomotor agitation and high‐risk behavior were not significantly elevated before suicidal behavior. Conclusions: Suicidal ideation, loss of interest and, to a lesser extent, anxiety may represent acute suicide risk factors up to four months before suicidal behavior in outpatients with bipolar disorder. Further investigation of these potential acute risk factors in prospective analyses is warranted.